The Effects of Maternal Depression on Children with Primary Monosymptomatic Nocturnal Enuresis - Bahar Çaran; Duygu Hacıhamdioğlu; Gamze Özgürhan (Cam & Sakura Medical Journal)
Objective: The effect of maternal psychosocial status on quality of life of children with primary monosymptomatic nocturnal enuresis (PMNE) has not been investigated. The aim of this study is to investigate the effects of maternal depression and demographic variables on the quality of life of enuretic children. Material and Methods: The study consisted of 58 children with PMNE between the ages of 6 to12 and their mothers. Participants were asked to complete the Pediatric Quality of Life Inventory and the Beck depression inventory (BDI). Results: Physical health total scores (PHTS) were correlated with psychosocial health total scores (PSHTS) (p=0.020, r=0.394) and mother’s age (p=0.025, r=0.162). Maternal age was negatively correlated with the BDI score (p=0.012, r=-0.328). PHTS was significantly lower in the group with primary education (p=0.043). In addition, maternal age and income were higher in the high school/university group (p=0.031, p=0.042, respectively). PSHTS was lower in children with mothers who had moderate mood disorders/clinical depression, than children of mothers with normal BDI scores (p=0.032). Conclusion: The results of this study indicate that mothers with moderate mood disorders and clinical depression directly affected the psychosocial health of their enuretic children and indirectly affected their physical health.